ASK THE PANEL. (Times Higher Education Supplement, 2005)
Offers advice on dealing with a university staff member who is a practising Christian and uses scriptural quotes as screensavers. Liability of an institution if an employee discriminates against or harasses another on the grounds of religion, belief or sexual orientation according to Great Britain's Employment Equality Regulations 2003; Approach that can be taken to ask a colleague to change the screensaver; Importance of informing colleagues that he is entitled to personal beliefs but cannot impose aspects that are offensive to others.